ORIGINALITY - CONDITION FOR PROTECTION OF SCIENTIFIC WORKS - Viorel ROŞ; Andreea LIVĂDARIU (Challenges of the Knowledge Society)
The Doctrine defines originality as a combination of fancy, audacity, individuality and novelty. This ensemble of ideas meant to define originality appeals to the patents/ certificates Law for which novelty/ innovation is not enough. It shall be accompanied by inventive activity. The aim of the paper below is to clarify the question of the scientific works originality, by referring to the two appearantly contradictory norms and to their consequences over counterfeit/ imitation.